Strategi Promosi, Diferensiasi dan Keputusan Pembelian pada Kepuasan Pelanggan - Masruroh Masruroh; Winda Suryadi (Bina Nusantara University, 2010)
Today every goods and services industry always tries to develop their comparative and competitive ability. Therefore the company no longer only think of profits but start to pay attention to other potential sectors that is able to sustain or increase revenue hence the customers interests becomes a major concern. The case study in this research is Promotion and Differentiation Strategy, on customer of PT Indomobil Trada National - Nissan Kelapa Gading. The purpose of this study is to analyze the influence of the Promotion and Differentiation Strategies of Buying Decision and Its Impact on Customer Satisfaction. The method used in this study is Path Analysis. This research produces the structural equation Y = 0.375 X1 + 0.560 X2 + 0.42 ε1 where R2 = 82.1% and Z = 0.381 X1 + 0.524 Y + 0.48 ε2 where R2 = 76.4%. Promotion and Differentiation Strategies is effective in providing a positive influence towards Buying Decision, as well as Promotion Strategy and Buying Decision which has positive influence towards Customer Satisfaction, but Differentiation does not significantly influence Customer Satisfaction, so we recommend PT Indomobil National Trada - Nissan Kelapa Gading further enhance the existing Promotion Strategy to enhance influence in inducing Customer Satisfaction.